Formation of Information Competence in Future Teachers based on the Integration of Artificial Intelligence Technologies in Education - Trapitsyn, Sergey; TURSYNBAEVA, AINUR (Pedagogy and Psychology, 2025)
The modern education system is undergoing a period of fundamental transformations driven by the rapid development of digital technologies and the widespread integration of artificial intelligence into educational practice. Traditional approaches to developing teachers’ information competence, based on mastering basic computer skills, prove insufficient for preparing specialists to work in the context of intelligent technology development. The integration of AI technologies in education actualizes the need to reconceptualize the content and structure of teachers’ information competence, incorporating new components related to understanding the principles of intelligent systems operation and skills for critically evaluating their capabilities. Methodology and Methods. The research is based on the analysis of theoretical works by leading domestic and foreign scholars in the field of teachers’ information competence and the application of artificial intelligence in education. Methods of theoretical analysis, systematization and generalization of scientific literature, and structural-functional analysis were used to identify components of information competence in the context of AI technologies. A comparative analysis of international standards and frameworks for teachers’ ICT competence was conducted. Results. The structure of teachers’ information competence has been defined as a multi-component system including cognitive, operational-activity, and motivational-value components. The interrelationship between the level of teachers’ information competence and the effectiveness of AI technology application in various aspects of professional activity has been identified: from lesson planning to creating an inclusive educational environment. It has been established that AI acts as a catalyst for the transformation of information competence, actualizing the development of new data handling skills and critical analysis of automated solutions. Scientific Novelty. For the first time, a comprehensive analysis of the transformation of teachers’ information competence under conditions of AI technology integration in education has been conducted. A theoretical model of the interrelationship between information competence components and various applications of artificial intelligence in pedagogical activity has been developed. The necessity of developing new digital age competencies in future teachers has been substantiated. Practical Significance. The research results can be used in developing educational programs for teacher training, creating teacher professional development systems, and forming standards of professional competence for educators in the context of digital transformation of education.